Implementasi Bahasa Inggris dengan Direct Method untuk Meningkatkan Motivasi Belajar Agama Islam Pada Santri Al-Hidayah Jorong Marambuang - Trisno, Bambang; Syawaluddin, Syawaluddin (SURAU : Journal of Islamic Education, 2023)
Abstract Motivation plays a significant role in education, as it encourages students to be diligent, industrious, enthusiastic in their learning, and to become individuals of high quality. However, at MDA Al-hidayah in Jorong Marambuang, there are still some students who lack enthusiasm and are somewhat lazy in their pursuit of Islamic education. This study aims to describe the importance of using the direct method to enhance the motivation of MDA Alhidayah Jorong Marambuang's students in learning Islamic religion. The research method employed is qualitative descriptive. The findings of this study illustrate that the implementation of the direct method has a significant positive impact on enhancing the motivation of the students. In this research, the students displayed increased enthusiasm, diligence, and zeal in studying Islam. The direct method appears to be successful in igniting their interest in religious education and encouraging them to be more dedicated in their pursuit of understanding Islam. These findings make a significant contribution in the context of religious education and the development of effective teaching methods.Â AbstrakMotivasi sangat berperan dalam pendidikan, dengan motivasi peserta didik akan tekun, rajin, bersemangat dalam belajar serta menjadi orang yang berkualitas. Namun pada MDA Al-hidayah Jorong Marambuangmasih ada santri yang malas-malasan serta kurang bersemangat dalam mempelajari agama Islam. Penelitian ini bertujuan untuk mendeskripsikan tentang seberapa penting penggunaan metode langsung (direct method) untuk meningkatkan motivasi belajar Agama Islam santri di MDA Alhidayah Jorong Marambuang. Metode yang digunakan adah kualitatif deskriptif. Hasil penelitian ini menggambarkan bahwa penerapan metode langsung (direct method) memiliki dampak positif yang signifikan dalam meningkatkan motivasi belajar para santri. Dalam penelitian ini, para santri menunjukkan peningkatan dalam antusiasme, ketekunan, dan semangat mereka dalam mempelajari agama Islam. Metode langsung ini tampaknya berhasil membangkitkan minat mereka dalam pembelajaran agama dan mendorong mereka untuk lebih berdedikasi dalam mengejar pemahaman agama Islam. Temuan ini memberikan kontribusi penting dalam konteks pendidikan agama dan pengembangan metode pengajaran yang efektif.